2001
DOI: 10.1038/sj.ijo.0801740
|View full text |Cite
|
Sign up to set email alerts
|

Increase of fat oxidation and weight loss in obese mice caused by chronic treatment with human growth hormone or a modified C-terminal fragment

Abstract: Both hGH and its C-terminal fragment reduce body weight gain, increase fat oxidation, and stimulate lipolysis in obese mice, yet AOD9604 does not interact with the hGH receptor. Thus, the concept of hGH behaving as a pro-hormone is further confirmed. This data shows that fragments of hGH can act in a manner novel to traditional hGH-stimulated pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…It is of interest that also smaller GH fragments stimulate energy expenditure and induce weight loss in animals (39). Intact GH may induce insulin resistance, at least initially.…”
Section: Effect Of Growth Hormone Therapy On Body Weight and Body Commentioning
confidence: 99%
“…It is of interest that also smaller GH fragments stimulate energy expenditure and induce weight loss in animals (39). Intact GH may induce insulin resistance, at least initially.…”
Section: Effect Of Growth Hormone Therapy On Body Weight and Body Commentioning
confidence: 99%
“…[4][5][6][7] Clinical and experimental investigations have shown that GH administration leads to the reduction in fat mass in GH-deficient individuals as well as individuals suffering from certain genetic forms of obesity, such as Prader-Willi syndrome, and in obese animal models, such as ob/ob mice, which display diminished GH secretion. [8][9][10][11] However, despite these positive effects of GH on adipose reduction, GH treatments of individuals with idiopathic obesity (not associated with an endocrinopathy or syndrome) have had little success, even though their GH levels are generally reduced. 12 These observations suggest that idiopathic obesity may be associated with GH resistance at the level of the adipocyte because of altered GHR expression.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The literature search furthermore identified 13 animal experiments qualifying for review. [36][37][38][39][40][41][42][43][44][45][46][47][48] The results in the text are reported as mean ± SEM unless otherwise noted.…”
Section: Literature Reviewmentioning
confidence: 99%